(untitled) (Journal of Applied Learning and Teaching, 2022)
This article focuses on the teaching styles and active teaching in East Africa in an attempt to examine what accounts for differences in performance between schools, and provide some lessons for sub-Saharan Africa. It uses data collected from 428 teachers in primary schools in Kenya; and 157 teachers in primary schools in Uganda. Assessment and classroom lesson video recordings of 436 lessons in math are used to generate evidence on patterns of teaching styles and active teaching. Results show that teaching practice in math is inclined towards the command and task styles that do not promote critical thinking among learners. The dominant teaching activity in math lessons was individual seat work in Kenya; and whole class chorus in Uganda. Overall, active teaching accounted for about half of the lesson time, with the other half being used in activities that do not directly enhance learning opportunities. After accounting for country-specific effects and the grade the teacher was teaching, teaching styles did not explain student performance in math, perhaps due to their ineffectiveness. The implications of these findings to the education systems in sub-Saharan Africa countries is the need to reinvigorate teaching practices; furthermore, any efforts to increase daily learning hours will be counterproductive as almost half of the lesson time is inefficiently utilized inside the classroom.